Safety and Efficacy of the C-117 Formula for Vulnerable Carotid Artery Plaques (Spchim): A Randomized Double-Blind Controlled Pilot Study. (17th July 2019) - Gong, Baoying; Chen, Xiuyan; Lin, Rongming; Zhang, Feng; Zhong, Jingxin; Zhang, Qixin; Zhou, Yuexiang; Li, Haijun; Zeng, Liling; Jiang, Zonghua; Guo, Jianwen
Abstract : Objective . To investigate the safety and efficacy of the Herbal Medicine C-117 (C-117) formula in the treatment of carotid atherosclerotic vulnerable plaques. Methods. This was a prospective, single-centre, randomized, double-blind study. A total of 120 eligible patients were randomly divided into two groups to receive the C-117 formula or placebo. As the basic treatment, both groups were treated according to the Guidelines for Secondary Prevention of Ischemic Stroke/Transient Ischemic Stroke in China using statins to regulate blood lipids, blood pressure lowering drugs, drugs for controlling blood sugar, and antiplatelet drugs according to the indications. The primary outcomes were the change in stability, the mean change of the plaque Crouse score, and the area and number of bilateral carotid artery plaques before and after 6 months of treatment. The secondary outcomes were the total number of cardiocerebrovascular events during the treatment and follow-up and the mean changes of lipid levels. Result . After 180 days of treatment, the plaque Crouse score(95% CI, 0.39 (0.01-0.77), P=0.046) and plaque area (95% CI, 2.14 (-10.10-14.39), P=0.727) were lower in the C-117 formula group than that before treatment. The plaque Crouse score of the control group (95% CI, 0.17 (-0.24-0.57), P=0.417) was lower than that before treatment, while the plaque area (95% CI, -0.35 (-9.35-8.65), P=0.938) increased, but without statistical significance. There was no significant difference in the reduction of the intima-media thickness (IMT), plaque Crouse score, or plaque area between the two groups after treatment (P>0.05). Subgroup analysis of patients whose Lipitor medication time ≥ 20% of the 6-month treatment showed that the levels of total cholesterol, triglycerides, and low-density lipoprotein were lower in the two groups after treatment than before, and the low-density lipoprotein levels in the C-117 formula group significantly decreased (95% CI, 2.99 (-0.08-0.39), P=0.005), but there was no statistical difference between the two groups after treatment (P>0.05). No serious adverse events occurred in the two groups after 180 days of treatment. Conclusion . The C-117 formula may be antiatherosclerotic by strengthening statins to reduce the low-density lipoprotein levels and reducing the carotid plaque Crouse scores. Clinical trials with large sample sizes, long-term interventions, and follow-up are needed to investigate the efficacy of the C-117 formula. Clinical Trials Registration . This trial is registered with clinicaltrials.gov identifier:NCT03072225 (registered retrospectively on 1st March 2017).